FAD2-DGAT2 Genes Coexpressed in Endophytic Aspergillus fumigatus Derived from Tung Oilseeds. (31st July 2012) - Chen, Yi-Cun; Wang, Yang-Dong; Cui, Qin-Qin; Zhan, Zhi-Yong
Abstract : Recent efforts to genetically engineer plants that contain fatty acid desaturases to produce valuable fatty acids have made only modest progress. Diacylglycerol acyltransferase 2 (DGAT2), which catalyzes the final step in triacylglycerol (TAG) assembly, might potentially regulate the biosynthesis of desired fatty acids in TAGs. To study the effects of tung tree ( Vernicia fordii ) vfDGAT2 in channeling the desired fatty acids into TAG, vfDGAT2 combined with the tung tree fatty acid desaturase-2 ( vfFAD2 ) gene was co-introduced into Aspergillus fumigatus, an endophytic fungus isolated from healthy tung oilseed. Two transformants coexpressing vfFAD2 and vfDGAT2 showed a more than 6-fold increase in linoleic acid production compared to the original A. fumigatus strain, while a nearly 2-fold increase was found in the transformant expressing only vfFAD2 . Our data suggest that vfDGAT2 plays a pivotal role in promoting linoleic acid accumulation in TAGs. This holds great promise for further genetic engineering aimed at producing valuable fatty acids.